'On the hunt for belonging': culture, hunting and indo-Muslim men in South Africa. Issue 1 (1st January 2019) - Kola, Azhar; Ratna, Aarti; Dashper, Katherine
ABSTRACT: Indian migrants have been moving to South Africa for the last 150 years. Yet, amidst the predominant Black-White racial binary operating from within South Africa, pre- to post-apartheid, very little is actually known about this heterogeneous and complex community of people. In this paper, we particularly focus upon the subjective realities of 10 Indo-Muslim men, in and through their involvement in the sport of hunting. Through the use of semi-structured interviews, we grapple with their changing senses of national identity and belonging, from relatively invisible outsiders to sporting insiders. The pleasures and positions of these sporting Indo-Muslim men though do not necessarily alter their 'middle-man' citizenship status in South Africa more broadly.